1959
DOI: 10.2134/agronj1959.00021962005100070011x
|View full text |Cite
|
Sign up to set email alerts
|

Stem Rust Resistant Variants in Irradiated Populations Mutations or Field Hybrids?1

Abstract: Synopsis The relatively large number of rust‐resistant mutants observed in the N2 coming from N1 plants not isolated in the Aberdeen nursery were not true Markton phenotype and it is suggested they are the result of field hybridization. There were no rust‐resistant mutants in the N2 population grown from isolated N1 plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1959
1959
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…It would hence be premature to classify the mutant as a dominant one. CALDECOTT et al (1959) have already shown that mutations for stem rust resistance in species of Avena and Triticum are rare in radiation experiments and that the high frequency of mutations reported by KONZAK (1956) is not realised when the M1 plants are grown in isolation. KONZAK (1959) as well as COOPER and GREGORY (1960) have, however, found in carefully planned experiments that mutations for disease resistance do occur in irradiated material but at a very low frequency.…”
Section: Resultsmentioning
confidence: 96%
“…It would hence be premature to classify the mutant as a dominant one. CALDECOTT et al (1959) have already shown that mutations for stem rust resistance in species of Avena and Triticum are rare in radiation experiments and that the high frequency of mutations reported by KONZAK (1956) is not realised when the M1 plants are grown in isolation. KONZAK (1959) as well as COOPER and GREGORY (1960) have, however, found in carefully planned experiments that mutations for disease resistance do occur in irradiated material but at a very low frequency.…”
Section: Resultsmentioning
confidence: 96%
“…Hence, this ratio which suggests dominance may not necessarily reflect the true genetic situation. 3 The offspring of this plant also varied considerably for a number of characters including growth habit, height, form, maturity, and seed type (too many for any possible hybrid). Such variation is probably due to unusual chromosomal recombinations or to duplications and deficiences associated with the induced sterility.…”
Section: Current Interpretation and Recent Resultsmentioning
confidence: 99%
“…On the contrary, the yielding ability of some resistant mutants exceeds that of the control. COOPER and GREGORY also compared their resull s to those obtained by CALDECOTT et al (1959) in oats. The latter authors found no resistant mutant in 1740 N, plants.…”
Section: Disease Resistancementioning
confidence: 99%